Research and Implementation of University Student Union Management System Driven by Informatization and Automation - FUYU, FUYU; GUFANG, GUFANG; Fahmi, Hasanul (IT for Society, 2024)
Taking this paper makes a detailed analysis and research on the student workflow based on SSM. First, from the point of view of software engineering, combined with the characteristics of software systems, software engineering analysis and design. Then, based on the introduction of SSM architecture, combined with Java technology and related development tools, the system implementation process is described in detail. Experimental results show that the system has high efficiency and quality. Firstly, the requirements of the system are analyzed, and the main functions and implementation process are determined. On this basis, the overall structure of the system is proposed, and the functions of each module are divided and processed. Then, the database management system based on MySQL is applied to backstage database, and the system is programmed by IDEA development tool. After the system design is completed, the system is tested in detail. The experiment proves that the system can realize the automation and management of students' working process effectively.